Altered Endocrine and Autocrine Metabolism of Vitamin D in a Mouse Model of Gastrointestinal Inflammation - Liu, Nancy (The Endocrine Society, 2008)
The active form of vitamin D, 1,25-dihydroxyvitamin D(3), [1,25(OH)(2)D(3)] has potent actions on innate and adaptive immunity. Although endocrine synthesis of 1,25(OH)(2)D(3) takes place in the kidney, the enzyme that catalyzes this, 25-hydroxyvitamin D-1α-hydroxylase (CYP27b1 in humans, Cyp27b1 in mice), is expressed at many extra-renal sites including the colon. We have shown previously that colonic expression of CYP27b1 may act to protect against the onset of colitis. To investigate this further, we firstly characterized changes in Cyp27b1 expression in a mouse model of colitis. Mice treated with dextran sodium sulfate (DSS) showed weight loss, histological evidence of colitis, and increased expression of inflammatory cytokines. This was associated with decreased renal expression of Cyp27b1 (5-fold, P = 0.013) and lower serum 1,25(OH)(2)D(3) (51.8 ± 5.9 pg/nl vs. 65.1 ± 1.6 in controls, P < 0.001). However, expression of CYP27b1 was increased in the proximal colon of DSS mice (4-fold compared with controls, P < 0.001). Further studies were carried out using Cyp27b1 null (−/−) mice. Compared with +/− controls the Cyp27b1 −/− mice showed increased weight loss (4.9% vs. 22.8%, P < 0.001) and colitis. This was associated with raised IL-1 in the distal colon and IL-17 in the proximal and distal colon. Conversely, DSS-treated Cyp27b1−/− mice exhibited lower IL-10 in the proximal colon and toll-like receptors 2 and 4 in the distal colon. These data indicate that both local and endocrine synthesis of 1,25(OH)(2)D(3) affect colitis in DSS-treated mice. Lack of Cyp27b1 exacerbates disease in this model, suggesting that similar effects may occur with vitamin D deficiency.